Cognitive Behavior Therapy (CBT) untuk Mengatasi Kesulitan Mahasiswa dalam Penyelesaian Skripsi - Pane, Riem Malini; Rizki, Putri Saima (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2023)
AbstractThis research aims to overcome the difficulties of students completing final assignments using a cognitive behavior therapy approach. The analysis applied is based on literature data that has been collected. Data is presented in narrative descriptive form. The results of this research are that counselors try to divert negative thoughts into positive thoughts, giving birth to objectivity and a sense of optimism. Apart from changes in thoughts, this therapy also continues with changes in behavior as a concrete step in overcoming problems. These two actions are carried out simultaneously so that students have positive habits in both cognitive and behavioral aspects. Cognitive and behavioral therapy is carried out with two interventions, namely cognitive intervention and behavioral intervention with four sessions, namely assessment sessions, cognitive therapy sessions, behavioral therapy sessions and cognitive therapy and behavioral therapy evaluation sessions.Keywords: Cognitive, Behavior, Therapy, Difficulty, Thesis AbstrakPenelitian ini bertujuan untuk mengatasi kesulitan mahasiswa yang menyelesaikan tugas kahir dengan pendekatan cognitive behavior therapy. Analisis yang diterapkan berdasarkan data-data literatur yang telah dikumpulkan. Data disajikan dalam bentuk deskriptif naratif. Adapun hasil penelitian ini adalah konselor berupaya untuk mengalihkan pikiran negatif menjadi pikiran positif, melahirkan obyektifitas dan rasa optimisme. Selain perubahan pada pikiran, terapi ini juga dilanjutkan dengan perubahan pada perilaku sebagai langkah konkrit dalam mengatasi masalah-masalah. Kedua tindakan ini dilakukan secara simultan sehingga mahasiswa memiliki kebiasaan positif baik dalam aspek kognitif maupun perilaku. Terapi kognitif dan perilaku dilakukan dengan dua intervensi, yaitu intervensi kognitif dan intervensi perilaku dengan empat sesi, yaitu sesi pengkajian, sesi terapi kognitif, sesi terapi perilaku dan sesi evaluasi terapi kognitif dan terapi perilaku.Kata Kunci: Cognitive, Behavior, Therapy, Kesulitan, Skripsi